Mixed-mode Zentangle and Pastel Nagomi artwork for improving mental well-being in university students during COVID-19 pandemic – a randomized controlled feasibility trial - Cheung, Kin; Ma, Ka Yan; Tsang, Hilda; Leung, Nok Hang; Lui, Ka Yee; Ho, Sze Wing (Frontiers in Psychology, 2023)
Background: University students are identified as a high-risk group for mental health problems. Artworks have been found effective in enhancing individuals’ mental well-being in different populations, but none have been conducted on university students. This study was to address this research gap to determine the feasibility and estimate the preliminary effect of two artworks - Zentangle art and Pastel Nagomi - for improving students’ mental well-being. Method: This was a 3-arm randomized controlled trial, with 33 undergraduates allocated to two eight-week artworks (Zentangle or Pastel Nagomi Art group) and a control group. Data were collected at baseline, and weeks 4, 6, 8, and 12. Focus group interviews were conducted at the 12-week follow-up. Results: The consent and attrition rates were 80.5% and 6.06% respectively. The attendance rate ranged from 83.3% to 100%. Compared with the control group, both interventions had positive effects on depression, self-efficacy, positive affect, anxiety and self-esteem; and Pastel Nagomi art even had a better sustainable effect on stress and perceived stress and a significantly decreased negative effect in week 6 and week 12 follow-up. The qualitative findings suggested that the intervention resulted in the participants enjoying the artwork process, and being proud of their artwork and personal growth. Limitation: The study included transfer students, who are generally more stressed than other students, which may have affected the results. Conclusion: The study suggests that both artworks are effective in improving undergraduates’ mental well-being and that it is feasible to conduct future large-scale studies.